2021
DOI: 10.1016/j.sjbs.2021.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of head lice (Pediculus humanus capitis) infestation among schools workers in the Eastern Region, Saudi Arabia

Abstract: In a cross-sectional survey in February-May 2019, the prevalence of Pediculosis capitis with demographic data and the behavioral practices were investigated among 750 participants in the Eastern region of Saudi Arabia. Female participation was highly remarked with a percentage of 94.08% compared to that of male one about 5.91%. A deficiency of knowledge about lice infestation was noted especially among illiterate participants raised from their socio-economic levels ( p -value = 0.001). L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Almost all the reported cases were of female patients, and original articles revealed that a significantly higher proportion of females than males demonstrated head lice infestations. 3 However, Hau and Muhi-Iddin reported the case of an 11-year-old male, with a haemoglobin level of 2.1 g/dl, who was suffering from a severe head lice infestation. 17 Fustino et al reported severe head lice infestation in a 12-year-old female with a haemoglobin level of 4.7 g/dl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all the reported cases were of female patients, and original articles revealed that a significantly higher proportion of females than males demonstrated head lice infestations. 3 However, Hau and Muhi-Iddin reported the case of an 11-year-old male, with a haemoglobin level of 2.1 g/dl, who was suffering from a severe head lice infestation. 17 Fustino et al reported severe head lice infestation in a 12-year-old female with a haemoglobin level of 4.7 g/dl.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study, female school workers constituted a significantly higher proportion of those infested with head lice than male school workers. 3 Head lice are typically transmitted through head-to-head contact, but they can also be transmitted through fomites. 4 They feed on human blood, but, in some cases, the parasite burden is high enough to cause iron deficiency anaemia (IDA).…”
Section: Introductionmentioning
confidence: 99%
“…Promoting excellent personal hygiene practices, such as frequent hair and body washing, can aid in preventing head lice infestations. Sharing personal things like combs, brushes, caps, and towels can further increase the likelihood of infection [2].…”
Section: Prevention and Controlmentioning
confidence: 99%
“…These tiny, wingless insects feed only on human blood and are spread by direct physical contact or the sharing of personal items such as hats, combs, and hairbrushes. The major species that infests the human scalp is Pediculus humanus capitis, often known as the head louse [2].…”
Section: Introductionmentioning
confidence: 99%
“…Hasil penelitian sebelumnya di dua sekolah menyatakan bahwa responden percaya bahwa frekuensi kebersihan pribadi dan mencuci rambut adalah metode terbaik untuk mencegah infestasi kutu [23]. Sebaliknya, hasil penelitian sitempat lain menyatakan tidak ada hubungan antara personal hygiene dan infestasi Pediculus humanus var.…”
Section: Pembahasanunclassified